2013
DOI: 10.3945/ajcn.112.051151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preterm birth and birth weight on eating behavior at 2 y of age

Abstract: Preterm children have more eating difficulties than term children do, but after adjustment for maternal and neonatal characteristics, gestational age is not associated with impaired eating behaviors at the age of 2 y. Female sex, a low maternal level of education, and less than -1 SD intrauterine growth are associated with eating difficulties at 2 y of age. This trial was registered at clinicaltrials.gov as NCT 00663572.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 22 publications
(24 reference statements)
7
83
0
10
Order By: Relevance
“…19,20,43 Some differences were found in feeding skills, between VP/VLBW and FT infants both early at term when sucking coordination is important 27,30,44 and after 6 months of age when processing of solids is required. 24,45,46 Consistent with previous research, no differences in sleeping patterns between very preterm and full-term infants during the first 6 months of life was found. 29,47,48 However, our finding that very preterm infants had increased odds of sleeping problems at 18 months contradicts findings of other studies.…”
Section: 42supporting
confidence: 90%
“…19,20,43 Some differences were found in feeding skills, between VP/VLBW and FT infants both early at term when sucking coordination is important 27,30,44 and after 6 months of age when processing of solids is required. 24,45,46 Consistent with previous research, no differences in sleeping patterns between very preterm and full-term infants during the first 6 months of life was found. 29,47,48 However, our finding that very preterm infants had increased odds of sleeping problems at 18 months contradicts findings of other studies.…”
Section: 42supporting
confidence: 90%
“…Migraine et al 17 reported in preterm infants a trend to have a lower food repertoire compared to full-term infants, which shows that this group presents more behavioral difficulties in relation to feeding. They also had less appetite and enjoyed their food less.…”
Section: Difficulties Experienced By Preterm Infants In Feedingmentioning
confidence: 99%
“…It also included aspects like parents' concerns about feeding, mealtime, and strategies used by parents and family to deal with the infant's behaviors. Similarly, Migraine et al 17 used another questionnaire validated in France, "Children's Eating Difficulties Questionnaire", which evaluated 4 dimensions: neophobia, selectivity, poor appetite and enjoyment of food. In addition, another questionnaire was used to collect information regarding the frequency of food intake and preference, which was applied in parents of 2-year-old infants.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Deux composantes psychologiques de la récom-pense sont sensibles à l'environnement nutritionnel : la satisfaction et la perception du plaisir (le liking), et la motivation consciente ou inconsciente à le reproduire (le wanting). Au niveau neurobiologique, les systèmes opioïdes, endocannabinoïdes et GABA (acide -aminobutyrique) gèrent le liking [17,18] et, pour le wanting, ce sont les systèmes opioïdes, la dopamine et ses interactions avec les comportement alimentaire considéré comme « difficile », car plus sujet à la néophobie 1 et au refus de diversifier leurs choix alimentaires [23]. Par ailleurs, l'étude d'une cohorte de 5 717 couples mère/enfant et 3 009 couples père/enfant montre une forte corrélation entre la consommation d'aliments gras par la mère et la préférence pour le gras chez l'enfant à 10 ans, alors qu'aucune corrélation n'existe avec le régime du père.…”
Section: Transposer Les éTudes Sur Les Modèles Animaux Et Les Rechercunclassified